Author Correction: Intravenous fluid therapy in critically ill adults. Issue 11 (November 2018) - Finfer, Simon; Myburgh, John; Bellomo, Rinaldo
Corrections: Fig. 1: 'MAP' inserted before '60–65 mmHg; Fig. 3: 'Echocardiography' amended to 'Electrocardiographic'. Fig. 4b additions: two cell nuclei; text labels 'Large pore transporting plasma proteins', 'Small pore network', 'Intercellular cleft'; 'Intact' and 'Damaged'; legend updated.